Hubungan Pengetahuan Ibu Tentang MP-ASI Dengan Praktik Pemberian MP-ASI Yang Benar - Sembiring , Elva Elvionita Br; Suyoko, Cica; Bidaya, Delni Suarsih; Tambunan, Jesika Triana; Paninsari, Debora (Journal of Pharmaceutical and Sciences, 2025)
Background: Complementary foods are designed to increase a baby's energy and nutrient intake because breast milk alone cannot meet the baby's daily nutritional needs. However, complementary foods must be introduced at the right time. The practice of providing complementary foods (MP-ASI) is a crucial step in fulfilling a baby's nutritional requirements. Objective: This study aims to determine the relationship between maternal knowledge about complementary foods and the proper practice of providing complementary foods. Method: This research employs a quantitative approach, specifically a correlation method with a cross-sectional design. The sample consists of 30 mothers with babies aged 6–12 months. Data analysis includes univariate and bivariate analysis using the Wilcoxon Signed Ranks Test. Results: Analysis of the N ties value revealed that 10 respondents showed an improvement in their level of knowledge after being provided with documentation on the proper provision of complementary foods. Based on the Wilcoxon test results, the p-value score was 0.004 (< 0.05), leading to the rejection of Ho and acceptance of Ha. Conclusion: There is a significant relationship between maternal knowledge about complementary foods (MP-ASI) and the proper practice of providing complementary foods. Mothers with a good understanding of complementary foods tend to provide them in accordance with correct guidelines, including food types, feeding timing, and presentation. In contrast, mothers with limited knowledge about complementary foods often fail to provide them appropriately, which can negatively impact the baby's nutritional status and development.